Coupled computational fluid mechanics/multibody dynamics approach for naval applications - Castro, Alejandro M. (2017)
The multibody dynamics (MBD) solver MagnusDyn and the computational fluid dynamics (CFD) code REX, both developed at the University of Iowa, are implicitly coupled. MagnusDyn can solve bodies connected through a variety of joints and cables, while REX is a dynamic overset naval hydrodynamics code with extensive capabilities for motions of surface and underwater vehicles including waves, autopilots and wind. The implementation adds capability to simulate at-sea operations, like takeoff and landing of manned and unmanned aircraft, deployment and recovery of service watercraft, etc. In these maneuvers, interaction between vessels occurs through connecting cables or direct contact. The paper describes the strategy to couple the solvers and presents validation and demonstration cases, including the relaxation of a buoy, and deployment and recovery of an unmanned underwater vehicle.